1991
DOI: 10.3171/jns.1991.74.6.0872
|View full text |Cite
|
Sign up to set email alerts
|

The risks of metastases from shunting in children with primary central nervous system tumors

Abstract: The authors reviewed the hospital charts of 415 pediatric patients treated for benign or malignant primary brain tumors over the past 20 years at the Children's Hospital Medical Center, Seattle. Patients' ages ranged from the neonatal period to 18 years. A shunt was placed in 152 patients (37%), 45 before and 94 after surgery. Confirmation of extraneural metastases was based on clinical and diagnostic examination. Factors analyzed as possibly influencing the occurrence of extraneural metastases were: 1) the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(68 citation statements)
references
References 44 publications
0
64
0
4
Order By: Relevance
“…Most frequently bone and bone marrow involvements are observed. [28] In our patients, no distant metastasis was detected.…”
Section: Discussionmentioning
confidence: 88%
“…Most frequently bone and bone marrow involvements are observed. [28] In our patients, no distant metastasis was detected.…”
Section: Discussionmentioning
confidence: 88%
“…This is especially true in cases of intraperitoneal metastases , in which meningeal dissemination has been documented in virtually every patien t. Once peritoneal metastases develop , they may or may not be associated with ascites(5) Berger et al (1) reported that no children with extraneural metastases developed ascites in the absence of a VP shunt and that pineal germ -cell tumors had a slightly increased incidence of abdominal dissemination with a VP shunt in place. Paine et al (6) found in 12 cases of germinomas with VP shunt metastasis that the principal site of VP shunt metastasis was related to the site of the distal aspect of the shunt tube , involving the peritoneal , retroperitoneal , and pelvic cavities.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is further complicated by the fact that a number of late-and end-stage brain cancer patients are in an immunocompromised state, due to leukopenia from myelosuppression following prior chemotherapy, or secondary to steroid treatment for edema control, which may lead to additional complications. Such frail patients are also at increased risk from anesthesia and may be at an increased risk of surgery-or shunt-related complications (18,40,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the fact that it is considered a minor invasive procedure, it does involve certain risks, such as hemorrhage, shunt malfunction, or infection (19)(20)(21); in addition, it may rarely result in peritoneal carcinomatosis due to seeding from the central nervous system (CNS) tumors (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Nevertheless, not all studies have encountered peritoneal seeding via VPS (16,30,40).…”
Section: Introductionmentioning
confidence: 99%